Development of Asthma Management Based on Health Belief Model in Parents - Sukartini, Tintin; Arsa, Sandi Alfa Wiga; Utami , Sri; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Asthma is chronic diseases which often happened in childhood, while parents are the key to control asthma by provide adequate education. This study aimed to increase belief in parents about asthma in their children who consists of four components that build beliefs. A quasi-experiment design with 33 samples parents of Children aged 6 - 11 with asthma. Measurement of belief in parents using the development of the Health Belief Model (HBM). The educational intervention given used an asthma-based childhood management module in the prevention of asthma relapse. MANOVA was used to determine the effect of management of asthma on belief-based children given to parents. Chi-square test showed no difference of respondent characteristic on education, occupation, age, asthma information and sex (p> 0.05). F group prices for Pillai Trace, Wilk Lambda, Hotelling’s Trace, and Roy’s Largest Root have significance values <0.001 (p <0.05). It showed a significant influence in every variables of the group on the component of the belief. Strength of the relationship also showed between the management of asthma in belief components, which were indicated by partial Eta Squared value, perceived susceptibility/seriousness (0.486), perceived benefit (0.547), perceived barrier (0,539), and self- 0.150) of parents. The education intervention for management asthma integration with HBM theory can be used as an alternative education all parents. Healthy behaviors that individuals do because of the belief about the benefits of a new activity, usually prevent the arrival of the disease.